2017
DOI: 10.18865/ed.27.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Intensive Care Unit Outcomes in African American Patients

Abstract: Obesity IntroductIonObesity defined by BMI ≥ 30 kg/ m 2 has increased in the United States in the last three decades. More than one-third of US adults were obese in 2012 1,2 and obesity is projected to rise to more than 50% by the year 2030. 3 While the overall prevalence of obesity has increased, significant racial/ ethnic disparities continue to exist; with highest prevalence found among non-Hispanic Black (47.8%) vs nonHispanic White (32.6%) adults. 1,4 As the prevalence of obesity increases, the numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A total of 199,421 subjects participated in the 23 studies, which consisted of 14 prospective [ 8 , 13 , 18 29 ] and 9 retrospective cohort studies [ 9 12 , 30 35 ]. Fourteen studies were from North America [ 9 , 10 , 12 , 13 , 19 , 20 , 21 , 25 , 27 , 28 , 30 , 32 34 ], one from South America [ 31 ], five from Europe [ 8 , 18 , 22 , 23 , 24 , 29 ], and two from Australia [ 26 , 35 ]. In seven studies [ 8 , 9 , 18 , 19 , 22 , 31 , 32 ], BMIs was classified only into obese versus non-obese ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 199,421 subjects participated in the 23 studies, which consisted of 14 prospective [ 8 , 13 , 18 29 ] and 9 retrospective cohort studies [ 9 12 , 30 35 ]. Fourteen studies were from North America [ 9 , 10 , 12 , 13 , 19 , 20 , 21 , 25 , 27 , 28 , 30 , 32 34 ], one from South America [ 31 ], five from Europe [ 8 , 18 , 22 , 23 , 24 , 29 ], and two from Australia [ 26 , 35 ]. In seven studies [ 8 , 9 , 18 , 19 , 22 , 31 , 32 ], BMIs was classified only into obese versus non-obese ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We assessed nonlinear association in 24 studies between BMI and the risk of mortality in the ICU. 13,14,16,19,27,28,[31][32][33]35,36,38,39,[40][41][42][43][44][45][46][47][48]49,53 Results showed a decrease in risk of mortality with an increase of BMI levels up to ≈35 kg/m 2 (P nonlinearity < .001). However, the risk of mortality increased in BMIs higher than 35 kg/m 2 (P nonlinearity < .001) ( Figure 3).…”
Section: Linear and Nonlinear Dose Responsementioning
confidence: 95%
“…Studies were conducted in different countries. Most studies were in the United States, 14,16,[27][28][29][30][31][32][33][34]35 whereas the remaining were from the United Kingdom, 36 France, 19,37 Korea, 38 Canada, Germany, [39][40][41] Italy, 42 Austria, 13,[43][44][45] the Netherlands, 46 Saudi Arabia, 47 Brazil, 48 and Japan. 49 Follow-up period was from 1 month to 11 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Still, obesity was signi cantly associated with longer length of stay and increased comorbid illness [28]. Recent studies are intended to evaluate the issue in larger study populations, among different subgroups, and according to the etiology context [26,29,30]. A recent dose-response meta-analysis regarding the effect of BMI on the mortality of ICU-admitted patients showed that for each unit of increase in BMI (kg/m2), a 0.6% decrease in mortality rate is expected [31].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a study conducted by Lewis et al, on the patients admitted to an adult medical ICU with a more than 24 hours stay, presented that the overweight and obesity were not related to ICU mortality. Still, obesity was signi cantly associated with longer length of stay and increased comorbid illness [28]. Recent studies are intended to evaluate the issue in larger study populations, among different subgroups, and according to the etiology context [26,29,30].…”
Section: Discussionmentioning
confidence: 99%